LASTing beyond the needle’s edge: A case of local anesthetic systemic toxicity following dorsal slit procedure - kiresur, vaishak; Hariprasad, K V; Kumar, Neeraja P (Indian Journal of Case Reports, 2026)
Local anesthetic systemic toxicity (LAST) is a rare but potentially life-threatening complication associated with the administration of local anesthetics. Early recognition and prompt management are crucial to achieving favorable outcomes. We report the case of a 34-year-old male who developed systemic toxicity following local anesthetic infiltration for a minor urological procedure. The patient presented with altered sensorium and hemodynamic instability and was managed successfully with supportive measures and lipid emulsion therapy. He made a complete recovery and was discharged on the 5th day. This case emphasizes the need for heightened awareness, early identification, and adherence to preventive strategies to minimize the risk of LAST, with lipid emulsion therapy remaining the cornerstone of treatment.